Nocebo-Hypothesis Cognitive Behavioral Therapy (NH-CBT) for Persons With Functional Neurological Symptoms (Motor Type): Design and Implementation of a Randomized Active-Controlled Trial - Richardson, Matt; Kleinstäuber, Maria; Wong, Dana (Frontiers in Neurology, 2020)
Introduction: Functional Neurological Symptom Disorders (FNSD) are associated with high levels of disability and immense direct and indirect health costs. An innovative multi-disciplinary rehabilitation approach for individuals with functional neurological symptoms of motor type – Nocebo-Hypothesis Cognitive Behavioral Therapy (NH-CBT) – combines CBT and movement retraining with video feedback embedded in a comprehensive explanatory model of the etiology of FNSD. Methods: This protocol describes the development and implementation of a phase II, parallel group, randomized controlled trial with blinded outcome assessors to compare the efficacy of NH-CBT with an active control condition (supportive counselling and movement retraining). Individuals meeting diagnostic criteria of an FNSD or psychogenic movement disorder will be randomly assigned to one of the 8-week interventions. Self-report scales of motor and other physical symptoms, symptom-related psychological variables and assessor ratings of participants’ mobility will be administered at baseline, and at 8-week and 16-week follow-up. Adverse events will be monitored across all sessions and therapeutic alliance will be measured at the end of therapy. The primary statistical analysis will test the hypothesis that NH-CBT is more effective than the control intervention at the 8-week follow-up. Discussion: The therapeutic strategies of NH-CBT are theory-driven by assumptions of the predictive-coding model of the etiology of FNSD. Core therapeutic strategies of NH-CBT are discussed in the context of this theoretical framework. Trial registration: Australian New Zealand Clinical Trials Registry (ANZCTR; identifier: ACTRN12620000550909)